Human intestinal microbiota composition is associated with local and systemic inflammation in obesity - Verdam, Froukje J.; Fuentes, Susana; de Jonge, Charlotte; Zoetendal, Erwin G.; Erbil, Runi; Greve, Jan Willem; Buurman, Wim A.; de Vos, Willem M.; Rensen, Sander S. (Obesity (Silver Spring, Md.), 2013)
Objective Intestinal microbiota have been suggested to contribute to the development of obesity, but the mechanism remains elusive. The relationship between microbiota composition, intestinal permeability, and inflammation in nonobese and obese subjects was investigated. Design and Methods Fecal microbiota composition of 28 subjects (BMI 18.6‐60.3 kg m−2) was analyzed by a phylogenetic profiling microarray. Fecal calprotectin and plasma C‐reactive protein levels were determined to evaluate intestinal and systemic inflammation. Furthermore, HbA1c, and plasma levels of transaminases and lipids were analyzed. Gastroduodenal, small intestinal, and colonic permeability were assessed by a multisaccharide test. Results Based on microbiota composition, the study population segregated into two clusters with predominantly obese (15/19) or exclusively nonobese (9/9) subjects. Whereas intestinal permeability did not differ between clusters, the obese cluster showed reduced bacterial diversity, a decreased Bacteroidetes/Firmicutes ratio, and an increased abundance of potential proinflammatory Proteobacteria. Interestingly, fecal calprotectin was only detectable in subjects within the obese microbiota cluster (n = 8/19, P = 0.02). Plasma C‐reactive protein was also increased in these subjects (P = 0.0005), and correlated with the Bacteroidetes/Firmicutes ratio (rs = −0.41, P = 0.03). Conclusions Intestinal microbiota alterations in obese subjects are associated with local and systemic inflammation, suggesting that the obesity‐related microbiota composition has a proinflammatory effect.